WORKSHOP PENCEGAHAN PERILAKU ANTI BULYING DI SD MOIN FEU KELURAHAN MANULAI 2 KOTA KUPANG - Adoe, Treesly; Taneo, Silvester P; Nawa, Netty E. A; Lala, Sofia Godheliva Un; Kota, Martha K; Koro, Maxsel (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Bullying behavior is a crime committed by children, so this behavior cannot be considered normal, because it will have a negative impact on the victim. Victims of bullying will feel depressed, insecure, afraid, worried and stressed when they come to school. The solution offered to the problem is by offering anti-bullying workshops at Moin Feu Elementary School, Manulai 2 Village, Kupang City. So the aim and expected benefits of this workshop are that teachers and students in grades IV and V have knowledge about bullying and can avoid bullying practices at Moin Feu Elementary School, Manulai 2 Village, Kupang City. The service methods applied in the activities are 1) lecture method, 2) presentations and small group discussions, 3) modeling and role play. The lecture method was chosen because this method will open up the understanding of activity participants to better understand the meaning of bullying, the types of bullying, the impact of bullying, as well as the forms of bullying prevention measures that can be taken. Furthermore, the presentation method and small group discussion is a combination method chosen with the consideration that these two methods can stimulate the activeness of PKM activity participants in discussing several bullying problems that occur at school, as well as finding solutions to solving these cases.